Facilitating students’ readiness for blended learning during the COVID-19 pandemic - Farani, Rizki; Budiningsih, C. Asri; Rohman, Arif (Institute of Advanced Engineering and Science, 2024)
Blended learning during COVID-19 pandemic creates diverse combination of face-to-face synchronous and asynchronous activities. However, there is still limited exploration on students’ readiness in terms of finishing their tasks. Most studies only focus on general description of students’ learning preparation. To complete the existing literature, we investigated the use of training, tutorials, and simulations to facilitate students’ readiness for blended learning during the COVID-19 pandemic. Three iterative phases of preparation, learning implementation, and investigating findings were employed in a frame of design-based research (DBR) method. The data consists of classroom’ observations, students’ reflective notes, and students’ achievements reports. All data were coded and analyzed statistically and qualitatively to determine the benefits of training, tutorials, and simulations in supporting students’ readiness to complete tasks. The results show that training, tutorials, and simulations facilitate extra asynchronous interaction and time to help students prepare their drafts for submission. Students can achieve all predefined learning goals at the end of the semester. The results imply that educators need to explore more initial activities prior blended learning to facilitate students’ readiness.